USING TUTORIAL VIDEO TO IMPROVE WRITING SKILLS OF THE NINTH GRADE STUDENTS OF MTS ALKHAIRAT LUMBUMAMARA DONGGALA - Nur Wahidah; Rofiqoh Rofiqoh; Afrillia Afrillia (e-Journal of ELTS (English Language Teaching Society), 2022)
The objective of this research is to find out whether the use of tutorial video can improve writing skills of the ninth grade students of MTs Alkhairat Lumbumamara Donggala or not. This research applied a pre-experimental research design. The sample was selected by using total sampling technique. They were 21 students of MTs Alkhairat Lumbumamara Donggala. This research was held in six meetings involved pre-test, treatment, and post-test. The data were collected by using writing test administered twice as pre-test and post-test. The finding showed that the mean score for pre-test was 62.26 while the mean score of post-test was 71.69. The results of data analysis revealed that the value of the t-counted (5.46) was higher than the value of the t-table (1.73) by applying a significant level of 0.05 with a degree of freedom (df) 21 (n-1). It means that the hypothesis is accepted. It indicates that the effect of using tutorial video is significant. In addition, the implication of this finding is can be concluded that using tutorial video was effective to teach writing procedure text because tutorial video can helped to practice their idea, also It helps the teachers transfer the materials that related to the lesson. It can give more detailed information about the object in the content. It could give imagination about the content of the tutorial video that is related to the materials.